Implementing a 'Safe Recovery' fall prevention program: Refining intervention theory using realist methods. (23rd April 2020) - Martin, Rachelle A.; Dickie, Benn; Skinner, Helen; Hurring, Sarah; Marshall, Rachel; Hanger, Hugh Carl
Abstract: Objectives: This research aimed to explain how the Safe Recovery Programme (SRP) may best work to reduce falls in older adults undergoing rehabilitation in four wards in an older person's health and rehabilitation service. Methods: Qualitative realist methods were used, including surveys completed by patients and staff, and qualitative interviews or focus groups exploring views of patients, ward staff and SRP educators. Results: Emphasising different types of information for patients with different pre‐existing understandings may facilitate their responses to SRP messaging. Consistency and coherence of SRP messaging within ward routines varied in response to staff SRP training and ongoing feedback mechanisms from SRP educators. Conclusions: Tailored individualised approaches for patients with specific characteristics may lead to patients being less likely to engage in risky behaviours. Staff training and processes for facilitating ongoing feedback between patients, SRP and ward staff are required to ensure consistency and coherence of SRP messaging.